Francisella Tularensis Clades B.FTN002-00 and B.13 Are Associated With Distinct Pathology in the European Brown Hare (Lepus europaeus). (November 2016) - Origgi, F. C.; Pilo, P.
Tularemia is a severe disease caused by Francisella tularensis . This bacterium has a major pathogenic potential in countless animal species as well as in humans. Despite the relatively significant body of literature available on this microorganism, many questions are still open concerning its biological cycle in the environment, the pathology and pathogenesis of the disease, the possible routes of infection in animals, and the pathologic and ecological relevance of the distinct phylogenetic clusters of F. tularensis . In order to address these questions, we have thoroughly characterized the pathology and microbiology of terminally ill European brown hares ( Lepus europaeus ) infected with F. tularensis subsp. holarctica, collected in Switzerland from 2012 to 2014. F . tularensis isolates were typed by defining their phylogenetic clusters. We showed that the pathology associated with F. tularensis subsp. holarctica belonging to the clade B.FTNF002-00 is different from that previously reported to be associated with the clade B.13. In particular, strains of the clade B.FTNF002-00 were almost invariably associated with splenitis and hepatitis and not with the polyserositis affecting pleura, pericardium, and kidney reported in the literature for infections caused by the clade B.13. We describe findings suggesting that the ports of entry for the bacteria might be the respiratory and digestive routes.